2015
DOI: 10.1080/00222933.2015.1006284
|View full text |Cite
|
Sign up to set email alerts
|

Description, molecular phylogeny, and natural history of a new kleptoparasitic species of gelechiid moth (Lepidoptera) associated with Melastomataceae galls in Brazil

Abstract: The male, female, pupa and larva of a new species of Gelechiidae (Lepidoptera), Locharcha opportuna Moreira and Becker, are described and illustrated with the aid of optical and scanning electron microscopy. A preliminary analysis of mitochondrial DNA sequences including members of related lineages is also provided. The immature stages are associated with galls induced by a species of Palaeomystella Fletcher (Lepidoptera: Momphidae) on Tibouchina sellowiana (Cham.) Cogn. (Melastomataceae), endemic to the Atlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 706 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In fact, during dissection of these galls we occasionally found an unidentified species of Coleoptera associated with them but only later in ontogeny; small, early developing galls always contained a larva of Andececidiumparrai . We believe that this beetle acts as a kleptoparasite (sensu Luz et al 2015), since apparently it does not change substantially the shape of the galls after usurping them. In addition, we found that galls of A.parrai may host other unidentified parasitoids, predators, and successors, thus being complex systems, similar to what has been previously demonstrated for Cecidoniuspampeanus (Moreira et al 2017).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In fact, during dissection of these galls we occasionally found an unidentified species of Coleoptera associated with them but only later in ontogeny; small, early developing galls always contained a larva of Andececidiumparrai . We believe that this beetle acts as a kleptoparasite (sensu Luz et al 2015), since apparently it does not change substantially the shape of the galls after usurping them. In addition, we found that galls of A.parrai may host other unidentified parasitoids, predators, and successors, thus being complex systems, similar to what has been previously demonstrated for Cecidoniuspampeanus (Moreira et al 2017).…”
Section: Discussionmentioning
confidence: 93%
“…This type of phenomenon may bring important taxonomic consequences, preventing the correct identification of the real inducer when such systems are undersampled. This situation is found for many gall-inducing insects, including other Lepidoptera (e.g., Morris 2000, van Noort et al 2007, Luz et al 2015). This was recently demonstrated in detail for Cecidoniuspampeanus Moreira and Gonçalves, a cecidosid moth whose identity was overlooked for more than one hundred years, as its galls had been erroneously described as induced by their hymenopteran inquilines (Moreira et al 2017).…”
Section: Introductionmentioning
confidence: 80%
“…Kleptoparasites in particular invade galls, usurping the cecidogenous species and become stationary, feeding upon gall tissues until they complete their larval development, and may prey upon the inducer and other insects that eventually enter the usurped gall (e.g., Morris et al 2000, Luz et al 2015). They do not induce differentiation and growth of new tissues, only feeding on those that were induced to develop by their precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Misidentification of the true gall inducers in such cases is obviously likely, since the inducer is eliminated from the system early in the gall ontogeny and no conspicuous trace of it may be left inside the gall. In addition, contrary to galls attacked either by kleptoparasites or inquilines that may stay attached to host plants, those free of them still containing the growing inducer may be dehiscent, with later development of immature stages occurring on the ground (e.g., van Noort et al 2007, Luz et al 2015). In this case, by altering the place of gall development in the field and thus enhancing the encounter of attacked galls by kleptoparasites and inquilines that stay attached to the host plant compared to free, detached ones, the possibility of missing the presence of the true inducers is substantially increased.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cecidophages may coexist with inducers by feeding internally or externally on the gall, and are lethal only when feeding on too much gall tissue, killing the inducer by starvation, or inadvertently opening up the gall. Kleptoparasitism is the only interaction where there is no possibility of coexistence with the inducer (Luz et al 2015).…”
Section: Coexistence With the Inducermentioning
confidence: 99%